2015
DOI: 10.1016/j.invent.2015.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of the combined effects of Web and Quitline interventions for smokeless tobacco cessation

Abstract: Background Use of smokeless tobacco (moist snuff and chewing tobacco) is a significant public health problem but smokeless tobacco users have few resources to help them quit. Web programs and telephone-based programs (Quitlines) have been shown to be effective for smoking cessation. We evaluate the effectiveness of a Web program, a Quitline, and the combination of the two for smokeless users recruited via the Web. Objectives To test whether offering both a Web and Quitline intervention for smokeless tobacco … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…This level of assessment completion is consistent with the follow-up completion results reported for other Web-based smokeless tobacco cessation intervention RCTs Danaher et al, 2014;Severson et al, 2008) and somewhat higher than some smoking cessation studies (e.g., Bricker et al, 2013;McKay et al, 2008;Munoz et al, 2009;Smit, de Vries and Hoving, 2012) but lower than others (e.g., Graham et al, 2011).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This level of assessment completion is consistent with the follow-up completion results reported for other Web-based smokeless tobacco cessation intervention RCTs Danaher et al, 2014;Severson et al, 2008) and somewhat higher than some smoking cessation studies (e.g., Bricker et al, 2013;McKay et al, 2008;Munoz et al, 2009;Smit, de Vries and Hoving, 2012) but lower than others (e.g., Graham et al, 2011).…”
Section: Discussionsupporting
confidence: 88%
“…They could be incorporated into stepped care tobacco cessation programs (Abrams et al, 1996) as well as an important option in established tobacco Quitline services (Abrams et al, 2010;Danaher et al, 2014;Graham et al, 2011). However, the cost of lozenges (their purchase price, shipping and handling costs) will need to be considered when deciding to use them as treatment adjuncts.…”
Section: Discussionmentioning
confidence: 99%
“…The combined Internet/phone arm outperformed the other two arms at the initial 3-month follow-up, roughly doubling the odds of abstinence, and maintained its advantage throughout the remaining 15-month of follow-up. In the smokeless tobacco trial, Danaher and colleagues (Danaher et al, 2015) randomized participants recruited online to Internet-only, Phone-only, Internet+Phone, or a self-help print control arm. ITT analyses showed that all three interventions outperformed the control, but that the combined Internet+Phone intervention did not outperform either the Internet-only or the Phone-only arms at both 3 and 6 months.…”
mentioning
confidence: 99%
“…Several studies point that there was a reduction of cigarette use in recent years after different government initiatives to decrease the prevalence of smokers [11][12][13] . According to a systematic review, group therapy is more effective than self-help to quit smoking, and nicotine replacement therapy doubles the chance of quitting 14 .…”
Section: Discussionmentioning
confidence: 99%